Antenna and system design for controlled delivery of microwave thermal ablation - Fallahi, Hojjatollah (Kansas State University, 2020)
Microwave ablation is an established minimally invasive modality for thermal ablation of unresectable tumors and other diseases. The goal of a microwave ablation procedure is to deliver microwave power in a manner localized to the targeted tissue, with the objective of raising the target tissue to ablative temperatures (~60 °C). Engineering efforts in microwave applicator design have largely been focused on the design of microwave antennas that yield large, near-spherical ablation zones, and can fit within rigid needles or flexible catheters. These efforts have led to significant progress in the development and clinical application of microwave ablation systems, particularly for treating tumors in the liver and other highly vascular organs. However, currently available applicator designs are ill-suited to treating targets of diverse shapes and sizes. Furthermore, there are a lack of non-imaging-based techniques for monitoring the transient progression of the ablation zone as a means for providing feedback to the physician. This dissertation presents the design, implementation, and experimental evaluation of microwave ablation antennas for site-specific therapeutic applications with these issues in mind. A deployable 915 MHz loop antenna is presented, providing a minimally-invasive approach for thermal ablation of the endometrial lining of the uterus for treatment of heavy menstrual bleeding. The antenna incorporates a radiating loop, which can be deployed to adjustable shapes within the uterine cavity, and a passive element, to enable thermal ablation, to 5.7–9.6 mm depth, of uterine cavities ranging in size from 4–6.5 cm in length and 2.5–4.5 cm in width. Electromagnetic–bioheat transfer simulations were employed for design optimization of the antennas, and proof-of-concept applicators were fabricated and extensively evaluated in ex vivo tissue. Finally, feasibility of using the broadband antenna reflection coefficient for monitoring the ablation progress during the course of ablation was evaluated. Experimental studies demonstrated a shift in antenna resonant frequency of 50 MHz correlated with complete ablation. For treatment of 1–2 cm spherical targets, water-cooled monopole antennas operating at 2.45 and 5.8 GHz were designed and experimentally evaluated in ex vivo tissue. The technical feasibility of using these applicators for treating 1–2 cm diameter benign adrenal adenomas was demonstrated. These studies demonstrated the potential of using minimally-invasive microwave ablation applicators for treatment of hypertension caused by benign aldosterone producing adenomas. Since tissue dielectric properties have been observed to change substantially at elevated temperatures, knowledge of the temperature-dependence of tissue dielectric properties may provide a means for estimating treatment state from changes in antenna reflection coefficient during a procedure. The broadband dielectric properties of bovine liver, an established tissue for experimental characterization of microwave ablation applicators, were measured from room temperature to ablative temperatures. The measured dielectric data were fit to a parametric model using piecewise linear functions, providing a means for readily incorporating these data into computational models. These data represent the first report of changes in broadband dielectric properties of liver tissue at ablative temperatures and should help enable additional studies in ablation system development.
Keywords: Microwave ablation; Endometrial ablation; Dielectric spectroscopy; Thermal ablation; Antenna design; Cancer